PENERBITAN SERTIPIKAT HAK MILIK ATAS TANAH SEBAGAI AKSES PERMODALAN BAGI USAHA MIKRO DAN KECIL DI KABUPATEN SIJUNJUNG - Ela Nurlaelawati; Iyah Faniyah (UNES Journal of Swara Justisia, 2017)
The certification of a land right for micro business and small is a government program which is implemented by National Land Agency (Badan Pertanahan Nasional). The program has purpose to provide certainty and legal protection for a right holder of a land and it is expected to alleviate the problems of micro business and small that do not have land right certificate. It can be committed by enhancing the access to capital of banks, so that, both of them can be more developed in order to improve people’s welfare. The findings of this study are based on two problems above. First, the issuance process of land right certificate for micro business and small in the district Sijunjung consists of pre-certification, certification, and post-certification. (1) Pre-certification of a land, is the authority of Department of Cooperatives, Industry, and Trade in the district Sijunjung. (2) Certification of a land right, is the authority of the National Land agency in the district Sijunjung. (3) Post-certification of a land right, is the authority of Department of Cooperatives, Industry, and Trade . Second, the implications of the issuance of land right certificate for both micro and small in the district Siunjung are: (1) ensuring legal certainty and legal protection for rights holders over land ownership, (2) providing the information required in performing legal acts of land affairs to related departments, (3) Resolve the land disputes, such as dispute of state administrative, civil, and criminal, (4) Land right certificate for micro and small owned by people or society can be used as collateral in banks to access the capital.